The girl from the tar paper school : Barbara Rose Johns and the advent of the civil rights movement - Kanefield, Teri, 1960- (Abrams Books for Young Readers, 2014)
Describes the peaceful protest organized by teenager Barbara Rose Johns in order to secure a permanent building for her segregated high school in Virginia in 1951, and explains how her actions helped fuel the civil rights movement.